2012
DOI: 10.1089/dia.2012.0010
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Telemedicine System with Automated Reminders on Outcomes in Women with Gestational Diabetes Mellitus

Abstract: Our enhanced telemedicine monitoring system increased system utilization and contact between women with GDM and their healthcare providers but did not impact upon pregnancy outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
151
1
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(164 citation statements)
references
References 19 publications
8
151
1
4
Order By: Relevance
“…Some studies conclude that telemedicine, through a more accurate and frequent monitoring, improves glycaemic control and reduces GDM complications [16,17]. But there is still some controversy in the area as other studies [13,[18][19][20] obtained that, although not inferior, telemedicine does not improve glycaemia values or neonatal outcomes compared to traditional care.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies conclude that telemedicine, through a more accurate and frequent monitoring, improves glycaemic control and reduces GDM complications [16,17]. But there is still some controversy in the area as other studies [13,[18][19][20] obtained that, although not inferior, telemedicine does not improve glycaemia values or neonatal outcomes compared to traditional care.…”
Section: Introductionmentioning
confidence: 99%
“…In 2012, a U.S.-based RCT (n = 80) demonstrated that adding interactive voice response to a telemonitoring system for pregnant women with multiple medical conditions ''increased system utilization and contact between women with GDM and their healthcare providers.'' 97 However, it had no impact on blood glucose values or infant birth weight. 97 GDM and Intermediate Outcomes (Weight, Diet, Exercise)…”
Section: Feasibility Of Gdm Telemonitoringmentioning
confidence: 96%
“…97 However, it had no impact on blood glucose values or infant birth weight. 97 GDM and Intermediate Outcomes (Weight, Diet, Exercise)…”
Section: Feasibility Of Gdm Telemonitoringmentioning
confidence: 96%
“…In total, 5 studies described an app for pregnant women with diabetes mellitus (type 1 or 2) or GDM [36,[39][40][41][42]. All studies in this subgroup evaluated an internet-based telemedicine system to monitor and transmit results to a health care professional.…”
Section: Effectiveness Of Medical Appsmentioning
confidence: 99%